A novel socially assistive robotic platform for cognitive-motor exercises for individuals with Parkinson's Disease: a participatory-design study from conception to feasibility testing with end users - Raz, Dor; Barkan-Slater, Shirel; Baum-Cohen, Ilanit; Vissel, Gal; Lahav-Raz, Yeela; Shapiro, Amir; Levy-Tzedek, Shelly (Frontiers in Robotics and AI, 2023)
The potential of socially assistive robots (SAR) to assist in rehabilitation has been demonstrated in contexts such as stroke and cardiac rehabilitation. Our objective was to design and test a platform that addresses specific cognitive-motor training needs of individuals with Parkinson's disease (IwPD). We used the participatory design approach, and collected input from a total of 62 stakeholders (IwPD, their family members and clinicians) in interviews, brainstorming sessions and in-lab feasibility testing of the resulting prototypes. The platform we developed includes two custommade mobile desktop robots, which engage users in concurrent cognitive and motor tasks. IwPD (n=16) reported high levels of enjoyment when using the platform (median = 5/5) and willingness to use the platform in the long term (median = 4.5/5). We report the specifics of the hardware and software design as well as the detailed input from the stakeholders.